Out-of-the-box: Learning to read and reading to learn. (September 2014) - James, Roger
Fifty years have elapsed since my primary education began with the 3 Rs – Reading, wRiting and aRithmetic. Since then there have been significant technological advances in writing and arithmetic with the mass introduction of the word processor and calculator. For reading, however, the technology and method remains the same. In the absence of a recognized model for our world, I have drawn on the popular science literature and my own calculations to propose a tariff of 10, 000 hours or 2000 books as the investment to acquire a new mastery. If these estimates are correct, the challenge for the information professional is how to optimize this investment.